Characteristics and Percentage of 30 Days All Cause Hospital Readmissions in Mongolia - Baasandorj, Lkhagvasuren; Altankhuyag, Ankhbayar; Erdenesaikhan, Enkh-Erdene; Shagdarsuren, Myagmarsuren; Batdelger, Garamgai; Tsagaankhuu, Sarnai; Lkhagvaa, Battur; Nyamdavaa, Khurelbaatar (Central Asian Journal of Medical Sciences, 2023)
Objective: This study aimed to estimate the 30 days readmissions and predictors of readmission at selected referral hospitals in Mongolia. Methods: We studied the electronic medical recording database of patients admitted to The State First Central Hospital of Mongolia, The State Second Central Hospital of Mongolia, and The State Third Central Hospital of Mongolia, from January 01, 2023, to June 30, 2023. The Institute for Healthcare Improvement’s Whole system measures white paper adopted the measurement methods for hospital readmission percentages. A descriptive analysis was conducted to calculate the percentage of hospital readmissions. We examined principal diagnoses, length of stay and age and gender are variables. Results: 31,675 hospital discharged data were recorded in hospitals over the 6-month study period. The average readmission percentage across the three hospitals were 1988 (6.3%). Most of the principal diagnosis leading to readmissions were cancer and chronic diseases. Conclusion: The highest hospital readmission rates were observed in patients with cancer and chronic diseases, particularly among individuals aged 46-64 years in the referral hospitals.